Report of the Arctic Ice Observing and Forecasting Program - 1970 - NAVAL OCEANOGRAPHIC OFFICE BAY SAINT LOUIS MS (1972)
The report contains a summary of Naval Oceanographic Office and Naval Weather Service ice operations during 1970. Describes operational aspects of obtaining and disseminating ice information and the ice forecasting and observing program. Ice charts including Danish data depict observed synoptic ice conditions throughout the year. Ice conditions interpreted from satellite photographs are included separately. Locations of oceanographic stations occupied in the polar and subpolar regions are included. See also report dated Aug 1970, AD877739.